2022
DOI: 10.3390/ijerph19031189
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Perception Change Associated with COVID-19 Vaccine’s Side Effects: The Role of Individual Differences

Abstract: The COVID-19 vaccine appears to be a crucial requirement to fight the pandemic. However, a part of the population possesses negative attitudes towards the vaccine. The spread of conspiracy theories and contradictory information about the pandemic have altered the population’s perception of risk. The risk-perception of the vaccine’s side effects may be affected by individual differences. The complex relationship between risk-perception and individual differences is relevant when people have to make decisions ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Fear of having serious or irreversible consequences after vaccination may be associated with the fear of death, increasing hesitancy. These results were consistent with other studies in which the main barriers to the COVD-19 vaccine were the perception of limited efficacy, potential adverse effects, and safety concerns [ 51 , 52 , 53 ]. Therefore, the present data suggested that a future information campaign should focus more on reducing the fear of side effects of vaccines than on enhancing their capacity to prevent infection.…”
Section: Discussionsupporting
confidence: 91%
“…Fear of having serious or irreversible consequences after vaccination may be associated with the fear of death, increasing hesitancy. These results were consistent with other studies in which the main barriers to the COVD-19 vaccine were the perception of limited efficacy, potential adverse effects, and safety concerns [ 51 , 52 , 53 ]. Therefore, the present data suggested that a future information campaign should focus more on reducing the fear of side effects of vaccines than on enhancing their capacity to prevent infection.…”
Section: Discussionsupporting
confidence: 91%
“…It is composed of six statements to be endorsed on a scale ranging from 1 = completely disagree to 5 = completely agree. The statements are: “Not knowing what's inside vaccines stops me from vaccinating my child”; “I am very concerned about possible serious and/or irreversible side effects that the vaccine may have on my child”; “Compared to before the start of the vaccination campaign, to date, I am very concerned about the side effects that the vaccine may have”; “I feel that I have no control over the choice to vaccinate my child”; “Most people close to me are against getting my child vaccinated”; “Taking appropriate precautions is already an adequate measure against COVID‐19.” Item construction was inspired by previous studies which had shown that similar beliefs (i.e., knowledge about vaccine; worries about unforeseen future side effects; mistrust of vaccine benefit; perceived lack of control over the vaccination choice; social pressure; preference for alternative protective measures) were linked to a negative attitude toward the decision to vaccinate themselves and their children (e.g., Colautti et al, 2022 ; Cookson et al, 2021 ; Facciolà et al, 2019 ; Fedele et al, 2021 ; Goldman et al, 2020 ; Martin & Petrie, 2017 ; Ruggiero et al, 2021 ). To confirm the construct validity a confirmatory factor analysis was conducted (for more details, see the results section).…”
Section: Methodsmentioning
confidence: 99%
“…Parents with a personal history of previous vaccinations against other diseases (i.e., influenza) turned out to be more prone to get their children vaccinated, even against COVID‐19 (Kelly et al, 2021 ), whereas overall concerns for both effectiveness and serious side effects of COVID‐19 vaccination decreased parents' intention to vaccinate their children (Ruggiero et al, 2021 ). A number of studies investigated the crucial role played by personal beliefs in COVID‐19 conspiracy theories (see Colautti et al, 2022 ; Đorđević et al, 2021 ; Howard & Davis, 2022 ; Pivetti et al, 2021 ) in undermining the COVID‐19 vaccination adherence. Accordingly, parents who are more prone to embrace conspiracy theories show greater levels of hesitation in having their children immunized (Cookson et al, 2021 ; Pisl et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is noted that the tourism-participation intention is often related to demographic characteristics that can impact the subjective probability judgments of residents, which then affects their behavior [47]. Specifically, factors such as age, education, gender, ethnicity, household income, and family structure can cause significant differences in the effects of PPT, which further influence their willingness to participate in PPT [48].…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%